Thyroid Hormone-Induced Expression of the Hepatic Scaffold Proteins Sestrin2, β-Klotho, and FRS2α in Relation to FGF21-AMPK Signaling - Videla, Luis A.; Vargas, Romina; Riquelme, Barbara; Fernández, Javier; Fernández, Virginia (Experimental and Clinical Endocrinology & Diabetes, 2018)
Thyroid hormone (3,3′,5-triiodothyronine, T3) accelerates energy metabolism in the liver through mechanisms involving upregulation of AMP-activated protein kinase (AMPK). This study aims to assess the influence of T3 on the expression of the scaffold proteins β-Klotho, fibroblast growth factor receptor substrate 2α (FRS2α), and Sestrin2 in relation to FGF21-AMPK signaling. Male Sprague-Dawley rats were given 0.1 mg T3/kg or hormone vehicle (controls) and studies were done 24 h after treatment. These include measurements of the mRNA expression (qPCR) of hepatic β-Klotho, FGF21, FGF21 receptor-1 (FGFR1), extracellular-signal-regulated kinase 1/2 (ERK1/2), FRS2α, ribosomal S6 kinase-1 (RSK1), liver kinase B1 (LKB1), AMPK, and Sestrin2. Also, protein levels of FGF21, FGFR1 (ELISA), and ERK1/2 (Western blot) were measured. T3 elicited a calorigenic response with higher hepatic mRNA expression of β-Klotho, FRS2α, and FGF21, increased serum FGF21, without changes in liver FGFR1 mRNA and its plasma levels. In addition, T3 enhanced ERK1/2 phosphorylation and the mRNA expression of ERK1/2, RSK1, LKB1, AMPK, and Sestrin2. T3 administration enhances liver FGF21-AMPK signaling involving upregulation of the scaffold proteins β-Klotho, FRS2α, and Sestrin2. β-Klotho and FRS2 induction favours the operation of the FGF21-FGFR1-β-Klotho complex as evidenced by the enhancement in ERK1/2 phosphorylation, whereas that of Sestrin2 recruits LKB1 to achieved AMPK activation, thus supporting a higher energy expenditure condition that may be desirable in some metabolic disorders
Keywords: thyroid hormone; liver; β-Klotho; Sestrin2; FGF21-AMPK signaling